Improving the Li-ion storage performance of commercial TiO2 by coating with soft carbon derived from pitch. (10th September 2016) - Wang, Li-Ying; Bai, Xue; Wu, Yan; Lun, Ning; Qi, Yong-Xin; Bai, Yu-Jun
Highlights: Commercial TiO2 nanoparticles were coated with soft carbon derived from pitch. The carbon-coated TiO2 exhibits outstanding electrochemical performance. The improved performance results from enhanced conductivity and interfacial Li + storage. Abstract: Commercial TiO2 usually exhibits poor electrochemical performance for Li-ion batteries. In this work, we fabricated the carbon-coated commercial TiO2 with soft carbon at 750 °C using pitch as the carbon source. The carbon-coated products reveal markedly enhanced capacity, excellent cyclability at a current density of 500 mA g −1 . The enhanced performance associates with the improved electronic and ionic conductivities results from the pitch-derived carbon with high graphitization degree as well as interfacial Li-ion storage.